TI_GERICHTE 12.2015.227 vom 13. März 2017 , Appalto - garanzia per difetti - risarcimento del danno - difetto estetico - TI Tribunale d'appello (2017)
Appalto - garanzia per difetti - risarcimento del danno - difetto estetico